Design optimization of a new supercritical CO2 single reheat coal-fired power generation system. (15th January 2022) - Tong, Yongjing; Duan, Liqiang; Yang, Ming; Pang, Liping
Abstract: Although supercritical CO2 (S–CO2 ) coal-fired paper generation systems have been studied broadly in recent years, there is still potential for further energy savings. A new system is proposed to efficiently use the waste heat of both the cooler and the boiler. The new system extends the air preheater surface area, uses the economizer to replace part of the heat load of the high-temperature recuperator, and both the evaporator and precooler are arranged before the cooler. The performance analysis model of the new system is built, and the effects of the economizer split ratio, the main compressor split ratio, and the operation load on the new system performance are investigated. The results show that the new system performance is much better than that of the reference system. Under the design condition, the boiler efficiency and the power generation efficiency of the new system are 96.3% and 49.5%, 1.1% and 2.6% higher than those of the reference system. There exist optimal split ratios for both the economizer and main compressor. The optimal split ratio of the economizer is 10%, and that of the main compressor is 70%. The power generation efficiency decreases with a decreasing operation load. Highlights: Energy-saving potentials of supercritical CO2 coal-fired power system are analyzed. A new system is proposed to solve waste heat utilization of both cooler and boiler. The new system cycle efficiency is 2.6% higher than that of the reference system. The new system boiler efficiency is 1.1% greater than that of the reference system. There exist optimal split ratios for economizer and compressor in the new system.